Calla Lily Hijab / Nur Syazwana Saiful Ridzuan and Nurul Najwa Fatihah Mohd Jamalludin - Saiful Ridzuan, Nur Syazwana; Mohd Jamalludin, Nurul Najwa Fatihah (2022)
Calla Lily Hijab is a newly established business in January 2022. Calla lily hijab has a very high goal, which is to sell hijabs at a very reasonable price. This is because Calla Lily wants all levels of society to be able to have hijabs that are reasonable in price and good quality. The name of Calla Lily is taken from the name of the flower, the owner gets an idea when they want to buy a flower. They found that the name of the flower was very interesting, therefore they took the name of the flower to make their own hijab brand. This business sells a variety of colour hijab, and the material of hijab is cotton, this type of hijab is called “bawal bidang 40”. All types of hijab colours are suitable for all women and Calla Lily hijab is often the focus among women who are teenagers and aged 20-40. This hijab is often the focus of people when it comes to the festival season, especially Eid. Not only that, the Calla Lily hijab is also a focus among college students. This is because the Calla Lily hijab is very minimal and suitable for college students. This business also offers cash on delivery (COD) for customers who live in Penang and Kedah and customers who are far away can use online transfer service.